1997
DOI: 10.1128/jb.179.17.5333-5339.1997
|View full text |Cite
|
Sign up to set email alerts
|

Leaderless polypeptides efficiently extracted from whole cells by osmotic shock

Abstract: Three molecular foldases, DsbA, DsbC, and rotamase (ppiA), exhibited the unusual property of accumulating in an osmotically sensitive cellular compartment of Escherichia coli when their signal sequences were precisely removed by mutation. A mammalian protein, interleukin-1 (IL-1) receptor antagonist, behaved in a similar fashion in E. coli when its native signal sequence was deleted. These leaderless mutants (but not two control proteins overexpressed in the same system) were quantitatively extractable from wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
45
0
1

Year Published

1998
1998
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(46 citation statements)
references
References 70 publications
0
45
0
1
Order By: Relevance
“…An interesting clue is provided by our finding that electroporation of cells, known to generate transient pores in biological membranes (19,24), causes selective release of the same subset of proteins, presumably passing through the same molecular sieve. Furthermore, solutions containing EDTA and a membrane-permeabilizing agent, such as Triton X-100 or polymyxin B, have been reported to extract from E. coli the same proteins as the osmotic shock procedure (23). It is tempting to speculate that the sudden swelling of the cytoplasm in osmotically shocked cells also leads to transient perforation of the plasma membrane.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An interesting clue is provided by our finding that electroporation of cells, known to generate transient pores in biological membranes (19,24), causes selective release of the same subset of proteins, presumably passing through the same molecular sieve. Furthermore, solutions containing EDTA and a membrane-permeabilizing agent, such as Triton X-100 or polymyxin B, have been reported to extract from E. coli the same proteins as the osmotic shock procedure (23). It is tempting to speculate that the sudden swelling of the cytoplasm in osmotically shocked cells also leads to transient perforation of the plasma membrane.…”
Section: Discussionmentioning
confidence: 99%
“…The subset of released cytoplasmic proteins also includes thioredoxin (1,17), molecular chaperone DnaK (6,8), and proteins involved in the biosynthesis of enterobactin (9), among others (5). Some foreign proteins expressed in the cytoplasm of E. coli have also been successfully extracted by the osmotic shock procedure (16,23).…”
mentioning
confidence: 99%
“…Procedures for restriction enzyme digestions, agarose gel electrophoresis, elution of DNA fragments from agarose gels, and separation of proteins using SDS-gel electrophoresis, phage P1 transduction, construction of deletion strains using the method of homologous recombination were carried out by standard procedures (25,26). Osmotic shock methods for preparing the periplasmic fraction and preparation of soluble and everted membrane vesicles by French press lysis were as described earlier (15,27). Protein was estimated by a modification of the Lowry procedure (28).…”
Section: Methodsmentioning
confidence: 99%
“…However, we found that standard procedures such as osmotic shock and sphaeroplast formation led to an unacceptable degree of cell lysis. Therefore, a method using Triton X-100 was selected, as it proved to reliably separate periplasmic and cellular fractions (Thorstenson et al, 1997). The purity of each fraction was assessed using antibodies against the periplasmic maltose-binding protein and the cytoplasmic enzyme β-galactosidase.…”
Section: Bfpu Is a Soluble Protein Partially Localized To The Periplasmmentioning
confidence: 99%